(untitled) (Research, Society and Development, 2024)
Early loss of primary teeth occurs due to lack of diagnosis and treatment in the early stages of caries disease. The aim of this study was to report the aesthetic and functional rehabilitation treatment of a 7-year-old male child with severe caries. During anamnesis, in addition to the complaint of pain when chewing, the child was embarrassed when talking and smiling. During the initial clinical examination, the upper arch showed carious lesions with intense coronal destruction in elements 52, 54, 55, 61, 62, 64, 65 and the absence of deciduous central incisor 51, while the lower arch showed extensive carious lesions in elements 73, 74, 75, 84, 85 and the absence of deciduous lateral incisor 72. After radiographic examination, the proposed treatment was extraction of teeth 52, 54, 55, 61, 62, 64, 65 and 75; restoration with composite resin in element 73; resin sealant in elements 16, 26, 36 and 46 and subsequent installation of upper and lower partial dentures. Guidance on oral hygiene and a non-cariogenic diet was given at all stages of treatment to encourage the child and family members to practice healthy habits. Based on the treatment carried out, it was concluded that the aesthetic-functional rehabilitation recovered the patient’s aesthetic and masticatory functions, helping to improve the child’s self-esteem and family satisfaction. The patient was referred to the medical service for treatment by a pediatrician and an otorhinolaryngologist.